LOGISTIC REGRESSION AS A MARKETING TOOL - Sargsyan, Siranush; Kharatyan, Alvard; Hovakimyan, Anna (Bulletin of Yerevan University G: Economics, 2019)
A properly selected marketing policy is one of the key factors in the growth of profitability of a firm. Thousands of companies and organizations today have their own official websites and can use the Internet for marketing purposes. With sentiment analysis, one can analyze user-generated records and quickly get information about the changing demands of customers without additional costs. The logistic regression model presented in the work can be used as a tool to increase the effectiveness of the firm’s marketing policy. We created software modules to download new records and to implement the builtin model that can be found on github.com (https://github.com/hripman/Armenian-corpus).